2015 IEEE 17th Electronics Packaging and Technology Conference (EPTC) 2015
DOI: 10.1109/eptc.2015.7412284
|View full text |Cite
|
Sign up to set email alerts
|

Development of high reliability lead-free solder joint dispersed IMC pillar

Abstract: The aim of this study is to create a high reliability solder joint for automotive applications by actively utilizing IMC formation in the joint. The method to disperse pillar-shaped

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…In the joint with Sn-5.0Sb, the die shear force increased with increasing bonding time regardless of the plate type. In the joint, formed IMCs grow and the number of IMCs increases with the increase of the bonding time [7]. As the result, the die shear force was improved by formation and growth of IMCs in the joint.…”
Section: Thermec 2016mentioning
confidence: 92%
See 2 more Smart Citations
“…In the joint with Sn-5.0Sb, the die shear force increased with increasing bonding time regardless of the plate type. In the joint, formed IMCs grow and the number of IMCs increases with the increase of the bonding time [7]. As the result, the die shear force was improved by formation and growth of IMCs in the joint.…”
Section: Thermec 2016mentioning
confidence: 92%
“…5(a), fracture occurred in the solder area including IMCs. The previous study has clarified that IMCs are coarsened with increasing bonding time changing their shapes from pillar-shaped to scallop-shaped [7]. When IMCs were coarsened, the dispersion strengthening of solder by IMCs reduced and thus die shear force decreased.…”
Section: Thermec 2016mentioning
confidence: 98%
See 1 more Smart Citation
“…Cu dissolved from the substrate forms a pillar shaped intermetallic compound (hereinafter referred to as an IMC pillar) in the soldered joint and the IMC pillar can suppress crack growth. On the basis of the quantitative analysis with an electron probe X-ray microanalyzer (EPMA), it was found that the IMC pillar consists of Cu and Sn [4]. The aim of this study is to investigate the formation mechanism of the IMC pillar.…”
Section: Introductionmentioning
confidence: 99%